Normal fault rupture propagation in overburdened rock and its impact on the ground deformation profile based on a model experimental approach - Wang, Tianqiang; Geng, Ping; Chen, Junbo; Li, Peisong; Yang, Qi; Yao, Chaofan (Soil dynamics and earthquake engineering (1984), 2023)
Rupture propagation and ground deformation are two major issues encountered during fault propagation. However, few studies have investigated the rupture propagation and ground deformation of a crossing fault field. In this study, three large-scale experimental tests for simulating normal faulting in crossing fault field were conducted to investigate the propagation characteristics and patterns of fault ruptures. In the conducted tests, different factors were considered, such as the fault dip Df, fault width Wf and amount of normal faulting h. The result revealed that the fault rupture pattern was mainly affected by Df, while Wf could affect the initial rupture length and ground tensioned cracks. Three fault rupture patterns can be distinguished under different Df values. In the former two patterns, the main fault rupture trace is in the form of a nonlinear logarithmic spiral line with an outcropping direction of 45°-ψp/2. Although the ground deformation profiles can be fitted roughly by empirical equation, the local deformations at fault fracture zone are not usually predicted well. The Gompertz function can describe the growth of ground settlement in a fault-crossing rock mass field. Therefore, Gompertz was introduced to characterize the growth and geometrical features of ground settlement due to normal faulting. Finally, bell-shaped ground slope curves were identified mathematically according to the first derivation of the Gompertz function. Based on the geometrical parameters, the ground deformation characteristics were furtherly revealed. This research would assist engineers in selecting sites and designing facilities in regions with weak fault fracture zones. •Propagation features of fault rupture in fault-crossing field.•Identification of fault rupture and geometrical characteristics.•Progressive ground failure process and relationship with fault ruptures.•Gompertz function fitting of ground deformation profile.•Ground deformation and failure characteristics.